HUKUM PENETAPAN BIAYA PENYIMPANAN EMAS DALAM AKAD RAHN PERSPEKTIF FATWA DSN-MUI NOMOR. 25/III/2002 - Nisma, Aulia; Hasanah, Uswatun (Legal Standing : Jurnal Ilmu Hukum, 2024)
Bank Syariah Indonesia (BSl) is a Sharia financial institution that helps the community in carrying out economic activities according to Islamic law. One of them is the implementation of gold pawning. Pawning (Rahn) in the Islamic view is property that is used as collateral for debts/loans that have been received. It is suspected that the implementation of sharia gold pawning at BSL is inconsistent with the provisions of DSN-MUI Fatwa Number. 25/DSN-MUI/III/2002 concerning Rahn. This research aims to find out how the gold storage costs are determined at Bank Syariah Indonesia KC S. Parman, as well as what the Fatwa law is regarding the implementation of gold pawning at BSI KCP S Parman. This research uses qualitative research methods sourced from research information obtained while conducting research at Bank Syariah KC S. Parman, and is supported by data that can be strengthened with literature as support. The results of the research show that, Sharia Gold Pawning at BSI KCP S Parman determines fees (ujrah) based on the loan size. The greater the cost of borrowing, the greater the storage costs. The implementation of determining marhun storage fees (ujrah) at BSI does not fully refer to the DSN-MUI Fatwa NUMBER 25/III/2002.